Assessment Model for facilitating digital retrofitting in manufacturing: key factors and practical insights - Alqoud, Abdulrahman; Milisavljevic-Syed, Jelena; Salonitis, Konstantinos (Elsevier, 2024)
In an era where factories are required to evolve or face obsolescence, digital retrofitting offers a lifeline to manufacturing companies striving to stay competitive. Digital retrofitting, the process of integrating cutting-edge technologies such as IoT components into legacy manufacturing systems, is emerging as a crucial strategy. However, due to the diversity of these legacy systems, a one-size-fits-all solution is ineffective. Despite the transformative potential of digital retrofitting, there is a noticeable gap in the tools that enable decision-makers to accurately assess their readiness for this process. To bridge this gap, it is essential to identify and evaluate critical factors that determine a system’s preparedness for integration with advanced technologies. This study proposes 21 key factors that must be considered to ensure readiness for digitalisation. These factors are grouped under four critical dimensions: strategy and organisation, workforce enhancement, smart factory, and smart process. Engagement with 18 industry practitioners was undertaken to validate these factors, ensuring their practical relevance. The findings provide valuable insights into the critical factors that need to be evaluated before embarking on the journey of digitalisation, ensuring that companies are fully prepared to integrate new technologies and optimise their manufacturing processes.
Keywords: 4014 Manufacturing engineering; Assessment model; Maturity model; Digital retrofitting; Industry 4.0; Manufacturing